From R&D to market: using trademarks to capture the market capability of top R&D investors - Carolina Castaldi; Mafini Dosso (European Commission, Joint Research Centre (JRC), 2018)
This paper investigates the links between the market capability of top corporate R&D investors (EU Industrial R&D Investment Scoreboards), as captured by trademark data and their economic performance in terms of net sales growth. It provides empirical evidence to better understand the extent to which companies, operating in different industrial sectors, combine technological capabilities with commercialization efforts to generate and appropriate the economic returns of their R&D investments. This paper shows how different dimensions of firms' market capabilities can be captured through trademark indicators. The results suggest that complementing R&D efforts and patenting activities with strong and specific market capabilities can indeed yield significant growth premiums. Moreover, offering services seems to pay off depending on the intensity of R&D investments. Yet, a quantile regression approach and a series of robustness checks indicate that such effects differ across the quantiles of the conditional sales growth distribution.
Keywords: O32; O34; L10; 330; R&D; trademarks; innovation; sales; services